Biosorption of Pb2+ from aqueous solution by rice straw modified with citric acid. Issue 2 (11th August 2015) - Guo, Lei; Liang, Lingyu; Wang, Yaojing; Liu, Mingda
Abstract : The rice straw, an enormous agricultural waste after harvest, was converted into biosorbent by using citric acid and sodium hydroxide for promoting its absorbability. The citric acid‐modified rice straw (CRS) was oriented to the potential utilization of removing Pb 2+ from aqueous solution. The Langmuir and Dubinin‐Radushkevich isotherm models were more appropriate to describe the Pb 2+ biosorption process. Zeta electric potential tests, FTIR, SEM, and XRD could characterize the physical‐chemical and morphological‐structural features of the biosorbent. Further analyses indicated that a great deal of negative charges, reactive functional groups and exchangeable ions which were introduced on the surface of adsorbent. The analyses of adsorption isotherm and thermodynamics revealed that the monolayer chemical adsorption accompanied ion‐exchange process might be the mechanism of the adsorption behaviors. The utilization of CRS might be a reasonable method for removal lead from wastewater. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 359–367, 2016